High rate amorphous and crystalline silicon formation by pulsed DC magnetron sputtering deposition for photovoltaics. Issue 1 (10th December 2014) - Bailey, Louise R.; Proudfoot, Gary; Mackenzie, Brodie; Andersen, Niels; Karlsson, Arne; Ulyashin, Alexander
<x xml:space="preserve">Abstract</x> Two methods of pulsed DC magnetron sputtering deposition have been used to form high rate, hydrogen‐free crystalline silicon layers. The first method is in situ crystalline silicon deposition. The second method is high rate amorphous silicon deposition followed by an anneal to induce crystallization. Over 20 μm thick crystalline silicon can be formed on wafers up to 200 mm round or 156 mm square. Two vacuum deposition systems were used for substrate cleaning and deposition. The crystallinity of silicon layers was analyzed by ellipsometry and Raman spectroscopy. Almost fully crystalline silicon is deposited in situ at table temperatures greater and equal to 650 °C. In situ crystalline silicon has been deposited at 40 nm/min and amorphous silicon can be deposited at over 400 nm/min subject to power density limitations for the silicon target. Up to 20 μm thick amorphous silicon deposited at room temperature is fully crystallized by annealing in vacuum on a 1000 °C table for 2 h. This work demonstrates that sputtering offers significant potential for depositing the absorber layer in silicon based photovoltaics.